Comparison of slaughter and carcass characteristics of ram, wether and ewe lambs - Kropf, Donald H.; Mackintosh, D.L.; Hinnergardt, L.C.; Flectcher, R.C.; Menzies, C.S.; Harrison, D.L.; Anderson, L. (Kansas Agricultural Experiment Station, 2011)
Lambs of known history were individually slaughtered as they attained 95 pounds live weight. Quality and quantity factors were evaluated and measurements taken after carcasses were chilled 48 hoours. Carcasses were broken into wholesale cuts and weights were obtained. Loin leg and loin were further trimmed of external fat to 3/8 inch thick and trimmed weights obtained.
Keywords: Lambs; Carcass characteristics; Dressing percentage; Slaughter characteristics